Analisis Faktor Minat Beli, Social commerce, Kepercayaan Dan Followers Dalam Pemasaran Produk Melalui Media Sosial Facebook Hijup - Suanggra Lilik Purwanti; Yusi Tyroni Mursityo; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
HIJUP is an Islamic fashion e-commerce. Based on the IPrice survey on e-commerce maps, HIJUP experienced a decrease in visitors in the third quarter to the fourth quarter, the decline in the number of visitors HIJUP illustrates the decline in consumer Purchase intention which makes HIJUP must improve effective and efficient marketing strategies to increase the number of visitors, causing consumer interest. Purchase intention is perceived by variables of trust, social commerce and followers. This study aims to describe existing variables using descriptive statistical analysis. Data collection was done by distributing questionnaires online to consumers who joined HIJUP's Facebook fanpage account and had purchased HIJUP products with a total of 82 respondents using purposive sampling technique. The very high category is in the Purchase intention and trust variables which means that consumers' Purchase intention and consumer confidence in HIJUP is very high, the high category is in followers and social commerce variables which means the influence of followers and social commerce on HIJUP facebook fanpage is high. Recommendations that can be given are increasing follower variables, ability indicators on trust variables, indicators of refractive interest, preferential on Purchase intention variables and increasing social commerce variables such as using endorse services.